Cyromazine affects the ovarian germ cells of Drosophila via the ecdysone signaling pathway - Khalid, Muhammad Zaryab; Sun, Zhipeng; Zhang, Jing; Zhang, Shijie; Zhong, Guohua (Frontiers in Physiology, 2022)
Cyromazine, an insect growth regulator, has been extensively used against the insect pests of livestock and household. Previously observed that the continuous selection of cyromazine from larval to adult stage decreased the number of germline stem cells (GSCs) in the adult ovary. Additionally, in this study, we observed that the number of Primodial germ cells (PGCs) were also decreased in the larval ovary after treatment with the cyromazine. However, the mechanism by which it affects the germ cells, is yet to be explored. Consequently, to deeply investigate the effects of cyromazine on the germ cells, we performed tissue-specific RNA-sequencing. Bioinformatic analysis revealed that ecdysone signaling pathway was involved and significantly got influenced under the stress of cyromazine. Based on which we screened and selected 14 ecdysone signaling responsive genes, and silenced their expression in the germ cells only. Results of which showed considerable reduction in the germ cells number. Furthermore, we mixed exogenous 20E with the cyromazine containing diet, to rescue the ecdysone signaling. Our results supported that the application of exogenous 20E significantly rescued the germ cells in the transgenic lines. Therefore, implying that the cyromazine decreased the number of germ cells by affecting the ecdysone signaling pathway.